TheraP: a randomized phase 2 trial of 177Lu‐PSMA‐617 theranostic treatment vs cabazitaxel in progressive metastatic castration‐resistant prostate cancer (Clinical Trial Protocol ANZUP 1603). (22nd October 2019) - Hofman, Michael S.; Emmett, Louise; Violet, John; Y. Zhang, Alison; Lawrence, Nicola J.; Stockler, Martin; Francis, Roslyn J.; Iravani, Amir; Williams, Scott; Azad, Arun; Martin, Andrew; McJannett, Margaret; et al.
Abstract : Objective: To assess the activity and safety of cabazitaxel chemotherapy vs that of treatment with 177 Lu‐PSMA‐617, a novel radiolabelled small molecule that binds with high affinity to prostate‐specific membrane antigen (PSMA), in men with metastatic castration‐resistant prostate cancer (mCRPC) who have received prior docetaxel treatment. Patients and methods: The TheraP trial (ANZUP 1603) is an open‐label, randomized, stratified, two‐arm multicentre phase 2 trial comparing the activity and safety of cabazitaxel chemotherapy vs 177 Lu‐PSMA‐617 therapy in the treatment of men with mCRPC. Key eligibility criteria include prior docetaxel chemotherapy, rising prostate‐specific antigen (PSA) level, sufficient PSMA avidity, as defined by centrally reviewed 68 Ga‐PSMA‐11 and fluorodeoxyglucose (FDG)‐positron emission tomography (PET)/computed tomography (CT) with no discordant FDG‐avid PSMA‐negative sites of disease. Patients in the control group receive standard treatment with cabazitaxel (20 mg/m 2 ) i.v. every 3 weeks with prednisolone 10 mg daily orally, for a maximum of 10 cycles. Patients in the experimental group receive 177 Lu‐PSMA‐617 (8.5 GBq decreasing by 0.5 GBq per cycle) i.v. every 6 weeks, for up to a maximum of six cycles. In the event of an exceptional response as defined on centrally reviewed post‐therapy single‐photon emission CT imaging, treatment will be suspended but can recommence on progression. The trial aims to include 200 patients who will be centrally randomized to one of the two treatment groups, in a 1:1 ratio. The primary endpoint is PSA response. Secondary endpoints are overall survival, progression‐free survival (PFS), radiographic PFS, PSA PFS, objective tumour response, pain response, pain PFS, health‐related quality of life, and frequency and severity of adverse events. The treatment and outcomes of patients excluded on the basis of low PSMA avidity or discordant FDG‐avid disease on screening 68 Ga‐PSMA‐11 and Fluorine‐18 ( 18 F)‐FDG‐PET/CT scan will also be assessed. Enrolment in the study commenced on 29 January 2018. Results and Conclusions: 177 Lu‐PSMA‐617 offers a potential additional life‐prolonging treatment option for men with mCRPC. The results of this trial will determine, for the first time in a randomized design, the activity and safety of 177 Lu‐PSMA‐617, as compared with cabazitaxel chemotherapy in men with progressive mCRPC.